LANGUAGE ATTITUDES, SHIFT, MAINTENANCE: A CASE STUDY OF JAKARTAN CHINESE INDONESIANS - Vina Yuliana; NFN Yanti (Linguistik Indonesia, 2023)
Indonesia is a multilingual country with over 700 languages spoken by various cultural groups. Language shift and maintenance are two common and interesting phenomena to study in a multilingual society. Studies focusing on language on shift and maintenance in Indonesia have been conducted for two decades. Nevertheless, limited studies have been found regarding the language of co-existing ethnics who have lived in Indonesia for more than two generations, such as Arabic or Chinese. Chinese descents in Indonesia speak Chinese languages/dialects, such as Hakka, Teochew, and Hokkien (CHL, hereafter). This study aims to explore the CHL language shift and maintenance in the Chinese community and the contributing factors to the phenomena. This research adopted a mixed-method approach. The data were collected from 100 respondents who reside in West Jakarta and North Jakarta. The data were collected using a questionnaire adapted from Cohn et al. (2013) and Ryan and Giles’s (1982) language indexes and in-depth interviews. The questionnaire data were analyzed using descriptive statistics, and the interview data were analyzed using thematic analysis. The result showed that the majority of Jakartan Chinese Indonesian have shifted to Indonesian, and only 9% of them still fully maintain the use of CHL in the family. English is more frequently used and mixed with Indonesian. This study found that the contributing factors of language shift are the language’s domains and functionality and the family background. It was found that parents’ place of birth or origin, parents’ first language, parents’ language attitude and policy at home, the language contact with the extended family, and how the extended family values CHL are influential for language shift. The result implied an alarm for CHL loss in the Jakartan Chinese community.